Upaya Diplomasi Persuasif dalam Penyelesaian Sengketa Wilayah Kashmir antara India dan Pakistan - Arvi Octabiana; Aan Anisah; Muhammad Arvin Zakiy Fuadi; Syafiqa Nadhira Kusuma; Deriel Pratama Putra; Bintang Afifah Nailah Surya (Universitas Islam Indragiri, 2025)
The Kashmir conflict between India and Pakistan has been ongoing since 1947, making it one of the most complex territorial disputes in the world. The situation is exacerbated by colonial legacies, differences in national identity and religion, and the strategic interests of these two nuclear-armed nations. Various attempts at resolution, whether through diplomatic pressure, military action, or the involvement of international entities such as the United Nations (UN), have failed to produce a lasting peaceful resolution. An alternative approach known as persuasive diplomacy has emerged, with the UN playing an important role through the UNMOGIP mission responsible for monitoring ceasefire violations. However, the effectiveness of UNMOGIP has been limited by restricted access, mandate constraints, and a lack of cooperation, particularly from India following the 1972 Simla Agreement. The principle of self-determination through a referendum is often suggested as a peaceful resolution; however, its implementation is hindered by conflicting territorial claims and the domestic political landscape in both countries. The lack of mutual trust, the influence of local factions, and the continued exploitation of the Kashmir issue for domestic political gain further complicate the negotiation process. This study emphasizes that the effectiveness of persuasive diplomacy is significantly influenced by domestic political stability, willingness to compromise, and active support from the international community. Therefore, while persuasive diplomacy holds considerable promise for promoting peace, the existing structural and political obstacles mean that this strategy requires strong commitment from all parties involved, reforms within the international framework, and the adoption of a comprehensive approach that takes into account the historical context, collective identity, and aspirations of the Kashmiri people to achieve a fair resolution.